Pengaruh sarana dan prasarana di sekolah dasar terhadap peningkatan bakat yang dimiliki siswa - Arini, Dea; Rigianti, Henry Aditia (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2024)
Of course, schools are facilitated by buildings or places to gain knowledge, namely school buildings. Not only buildings but supported by various other aspects, such as goals, vision, mission, facilities, infrastructure, and human resources. Without these aspects it is the same as a goal that has been made by the School, it will not be achieved and it should not run perfectly. The purpose of this article is to find out the importance of facilities and infrastructure for the psychomotor aspects of students or the talents possessed by students. This research method uses observation, interviews, and documentation, using observation sheets. This data collection will be carried out at SDN Ngebel which is in Kasihan, Bantul for 2 days, namely Monday and Saturday, 15 and 20 May 2023. The subjects in this study were the Principal, Teachers, and Students of SDN Ngebel. SD Ngebel has 2 class classes, namely A and B, for student respondents they can take either class A or B classes from class V. The results of this study are that school facilities and infrastructure are very important for supporting the success and learning process at school, especially in increasing talent owned by each student. One of them is with the school being able to take part in various competitions and win at various levels.